UTILIZATION OF INFORMATION TECHNOLOGY AS A MEDIUM FOR POLITICAL COMMUNICATION IN INDONESIA - Jajang Nurzaman (Komunika, 2024)
Society uses information technology to participate in politics in various ways. Problems that need to be considered in terms of cybersecurity, disinformation and hoaxes, unequal access and inadequate regulations. This study aims to identify and analyze the use of information technology as a political communication medium in Indonesia. This study uses a qualitative research approach with descriptive analysis techniques. Qualitative research methods are research approaches that are carried out descriptively, do not involve measurement, and aim to understand social phenomena in their natural context. This method focuses more on interpreting the meaning of the data obtained, as well as exploring a deep understanding of relationships and dynamics within a context. The results of the study found that information technology can be used as a political communication medium. This can be used by politicians, officials, political parties and the public in conveying their aspirations. However, on the other hand, this can give rise to the potential for cybercrime such as the spread of hoaxes, sara-based bullying and other cybercrimes.